A case of recurrent severe pre-eclampsia associated with essential cryofibrinogenaemia - Chau, Katrina (Obstet Med, 2017)
Essential cryofibrinogenaemia is a rare disorder characterized by cryofibrinogens without cryoglobulins. Connective tissue disorders and thrombophilia are known to increase risk of pre-eclampsia, but pre-eclampsia has not previously been reported in association with cryofibrinogenaemia. We report the case of a 32-year-old woman with recurrent severe pre-eclampsia diagnosed with essential cryofibrinogenaemia.